Programmed death ligand 1 expression and tumor-infiltrating lymphocytes in glioblastoma - Bergmeister-Berghoff, Anna Sophie; Kiesel, Barbara; Widhalm, Georg; Rajky, Orsolya; Ricken, Gerda; Wöhrer, Adelheid; Dieckmann, Karin; Filipits, Martin; Brandstetter, Anita; Weller, Michael; Kurscheid, Sebastian; Hegi, Monika E.; et al. (Neuro-Oncology, 2015)
AbstractBackground. Immune checkpoint inhibitors targeting programmed cell death 1 (PD1) or its ligand (PD-L1) showed activity in several cancer types.Methods.